2007
DOI: 10.5194/npg-14-123-2007
|View full text |Cite
|
Sign up to set email alerts
|

Time-scale invariant changes in atmospheric radon concentration and crustal strain prior to a large earthquake

Abstract: Abstract.Prior to large earthquakes (e.g. 1995 Kobe earthquake, Japan), an increase in the atmospheric radon concentration is observed, and this increase in the rate follows a power-law of the time-to-earthquake (time-to-failure). This phenomenon corresponds to the increase in the radon migration in crust and the exhalation into atmosphere. An irreversible thermodynamic model including time-scale invariance clarifies that the increases in the pressure of the advecting radon and permeability (hydraulic conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Moreover, the similar tendency is shown from the analysis of the daily minimums ( Fig. 2 in Kawada et al, 2007). Therefore we consider the anomaly during the three periods to be seismic related.…”
Section: Preseismic Radon Emanation Into Atmospheresupporting
confidence: 49%
See 2 more Smart Citations
“…Moreover, the similar tendency is shown from the analysis of the daily minimums ( Fig. 2 in Kawada et al, 2007). Therefore we consider the anomaly during the three periods to be seismic related.…”
Section: Preseismic Radon Emanation Into Atmospheresupporting
confidence: 49%
“…The change relates to the damage process in the crust (e.g. Ben-Zion and Lyakhovsky, 2002;Turcotte et al, 2003), and being a critical phenomenon prior to large earthquakes, shows a time-scale invariance, i.e., the temporal power-law (Kawada and Nagahama, 2006;Kawada et al, 2007). Furthermore, the inflection point in Fig.…”
Section: Preseismic Radon Emanation Into Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…(2004b) found that the critical characteristics of EM were determined by the nonlinear multi-fracture of discrete materials. From the thermodynamic view of irreversible damage evolution, Kawada et al (2007) introduced dipoles and explained the critical phenomena of EM emission and their timescale invariance theoretically. This research is of significance for the explanation of EMR critical characteristics before seismic events or during rock fracture.…”
Section: S Hu Et Al: Spatiotemporal Multifractal Characteristics Ofmentioning
confidence: 99%
“…The critical phenomena and fractal characteristics of EMR have been observed before seismic or rock fracture Rabinovitch et al, 2001;Kapiris et al, 2003;Uritsky et al, 2004;Kapiris et al, 2004a, b;Gotoh et al, 2004;Eftaxias et al, 2007;Muto et al, 2007). Some scholars have considered that the critical phenomena of EM emission are related to crack opening and expansion, as well as fractal structure Nanjo and Nagahama, 2004a, b;Kapiris et al, 2004a, b;Morgounov and Malzev, 2007;Kawada et al, 2007;Minadakis et al, 2012). Uritsky et al (2004) proposed a simple framework for modeling ultra-low frequency (ULF) electromagnetic emission signals associated with abrupt changes in the large-scale geometry of stress distribution before characteristic seismic events.…”
Section: Introductionmentioning
confidence: 99%